POSSIBILITIES OF FORMATION OF PEDAGOGICAL COOPERATION IN THE GROUP OF CHILDREN OF PRESCHOOL AGE - Yarmanova Yulduz Buriyevna; Gaybullaeva Sitora Abdullo qizi (Scholars Digest Publishing, 2024)
This article provides information on cooperation in the environment of children in team relations. In particular, the purpose of organizing joint activities among pupils of preschool educational organizations based on moral values is to direct the mutual relations of pupils towards morality. Through this, children develop a sense of mutual respect for their peers. Also, the fact that children's actions are focused on each other helps them find their place in this process.
Keywords: child, person, team, collective attitude, social, preschool age, preschool education, moral qualities, individual, individuality.